Soil Physicochemical Properties Variation under Annual Crop and Coffee Landuse in the Chentale Watershed, Upper Blue Nile Basin, Ethiopia - Feven Azene Tebekew; Teshome Betru Tadesse; Desta Adane Alemu; Amsalu Awoke Ayalew (Applied and Environmental Soil Science)
A detrimental decline in soil fertility has been attributed to losses in arable land productivity in Ethiopia. In this line, several studies were conducted to enable informed decisions; however, monitoring soil property dynamics in different biophysical, climatic, and cropping systems is yet to be adequate to support and influence decision and policymakers. To this end, this study evaluated soil physicochemical properties on land managed for annual crops and coffee land use in the Chentale watershed, the upper Blue Nile basin, Ethiopia. About 24 soil samples were collected from the two land uses and soil depths (topsoil: 0–15 cm and subsoil: 15–30 cm) with 6 replications for soil properties analysis. The result showed that most of the soil parameters varied significantly with land uses and were higher with coffee landuse (p<0.01) than with cropland. Furthermore, a neutral pH range, clay loam texture, medium level of organic matter (3.93%) and nitrogen (0.18%), high level of available phosphorus (23.35 PPM), and high to very high level of exchangeable base were recorded from coffee landuse than from cropland. Whereas the mean values of organic matter (OM) and total nitrogen (TN) decreased significantly (p<0.05) decreased in the subsoil. However, most of the physical and chemical properties of the soil did not vary significantly with depth. Moreover, low pH, low OM content, and low TN are the main properties of soil considered constraints of soil fertility in cropland at both depths. Therefore, it is recommended to maintain agroforestry practices, reduce the intensity of tilling, and supply organic materials to sustain the productivity of cropland.